Agreement To Impose French Protection On The Far Maghreb 1902 -1912 - علاء الدين, إبراهيم; لايقة, رامي; عيزوقي, رامي (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
Morocco represents the western wing of the Arab world, and the accession of these countries to the fold of the Arab nation and the spread of the Islamic religion and Arab culture and blood in it at an early date, so, these countries were dyed in Arabic, and the Maghreb countries gave Islam great services, including carrying the flame of the new religion and Arab civilization to the heart of Africa and even to Europe. The Arab Maghreb site had an impact on its history. Its location, far from the center of the Arab caliphate in Baghdad or elsewhere, made room for the splinter elements of the caliphate. Morocco Al Aqsa was subjected, like the Arab countries, to dule protection, the signs of which appeared in the Far Maghreb since the beginning of the twentieth century. Colonial empires to achieve their interests, and France made concessions that were not in its calculations in order to preserve its colonies in north Africa. And if the Portuguese and the Spanish opened this colonial page in the fifteenth century with successive attacks on the Moroccan gaps overlooking the Mediterranean and the atlantic ocean, the nineteenth century witnessed other waves represented in the activity of the maritime powers and other great powers that started to enter the field of colonialism. The French, the English, the Italians, and the Germans in particular competed in extending their influence over the countries of the Arab Maghreb, but the French are more than working hard to extend their protection to the far Maghreb in order to complete its control of all its countries and concluded agreements with the rest of the colonial European countries to divert them from this region.